Analysis of the Effect of Workload and Job Rotation on Employee Motivation and Its Impact on Employee Performance at the Tax Office - Maulana, Irvan; Eddyono, Fauziah (Journal of Applied Management Research, 2025)
In an effort to achieve tax revenue targets, the Ministry of Finance of the Republic of Indonesia has implemented an employee rotation policy to meet the human resource needs required to operate systems in modernized offices. A direct consequence of this effort to increase tax revenue is the anticipated rise in task volume and job complexity that employees must handle. This study aims to analyze the impact of workload and job rotation on employee motivation and its effect on employee performance. The subjects of this study are employees at the XYZ Primary Tax Office. The sampling technique used is a saturated sample. Data were analyzed using the Structural Equation Modeling (SEM) method, processed through the Smart PLS application. The research findings indicate that a high workload and excessively frequent job rotations can reduce employee motivation and negatively impact employee performance.